The relationship between student testwiseness and test scores among form one students in Dadaab Refugee Camp,Kenya - Surum, Janet (IJRDO- Journal of Educational Research, 2017)
The magnitude with which test scores are regarded in Kenya makes KCSE and KCPE a matter of life and death for kenyans. The purpose of the study therefore was to determine the relationship between selected personal and socio-contextual factors and test scores among form ones students in Dadaab Refugee Camp, Kenya. The study was guided by the following theory: Social cognitive learning by Albert Bandura. The study adopted a correlational design in order to be able to investigate and analyze the relationship between student testwiseness and form one test scores. It also used simple regression to find out whether the various variables would predict test scores. The study was conducted in four public schools of Dadaab refugee camps in the North-Eastern part of Kenya. The target population consisted of students and teachers. The sampling technique was that of convenient, purposive and systematic sampling in that order, where thirty five participants were selected from each school, to sum up to one hundred and thirty eight form one students and a total of thirty four teachers. Research instruments included questionnaires for teachers and students, while interview schedule was for teachers. The results revealed that there is a positive and significant relationship between student test wiseness and test scores.